Time trends in avoidable cancer mortality in Lithuania 1992–2008 - SMAILYTE, Giedre; PAREIGIS, Laurynas (Acta medica Lituanica, 2011)
Background. This study was aimed to evaluate achievements of medical health careservices in Lithuania by analysing time trends in avoidable cancer mortality of the whole Lithuanian population from 1992 through 2008.Materials and methods. Data of the Lithuanian Cancer Registry for 1992–2008 were used to analyse avoidable cancer mortality trends. Mortality rates for all cancer and selected cancer sites were analysed. Age-standardised rates were calculated for both sexes. The age of the study subjects ranged between 5 and 75 years. The corresponding population data by age, sex and year were available from the StatisticsLithuania.Results. Cancer mortality has been decreasing continuously over time in both sexes. The degree of reduction in all-site cancer mortality was slightly higher in women (by 1.03% per year) than in men (by 0.83% per year). Mortality avoidable by medical intervention has been continuously decreasing since 1992 in both sexes by more than 2% per year, while mortality avoidable by primary prevention decreased only in men. Cancer mortality avoidable by secondary prevention was decreasing in women and increasing in men.Conclusions. In Lithuania, a remarkable reduction in avoidable cancer mortality over the past decade has been found. However, the rate of reduction was slower in mortality avoidable by primary or secondary prevention methods than in mortality preventable by direct medical care, indicating that there is a need to put more effort towards primary and secondary prevention.Keywords: avoidable death, cancer mortality, quality of health care